MEMPOPULERKAN PROSEDUR HAK CUTI HAID DAN IMPLIKASI HUKUMNYA BAGI PEKERJA PEREMPUAN DI INDONESIA - Nail, Muhammad Hoiru (Ahkam: Jurnal Hukum Islam, 2023)
Female workers get privileges in the form of menstruation leave rights which are not owned by male workers. This privilege is certainly not a form of discrimination in the world of work but is a strong consideration of the biological nature of female workers. The problem that will be studied is how the flow/steps for applying for menstruation leave for female workers and what are the legal implications if the company does not exercise the right to leave for menstruation. The methodology used is normative legal research. Female workers are required to have a doctor’s certificate as a condition for applying for menstruation leave at the company, there are criminal sanctions and fines that can be threatened with companies that do not give permission for menstruation leave for female workers.